Four new secoiridoids from the stem barks of Syringa reticulata (Bl.) Hara. Issue 19 (21st September 2022) - Guo, Shuang; Liu, Yan; Sun, Yan-Ping; Pan, Juan; Guan, Wei; Li, Xiao-Mao; Wang, Si-Yi; Algradi, Adnan Mohammed; Yang, Bing-You; Kuang, Hai-Xue
Abstract: Four new secoiridoids, syrretoside A (1 ), syrretoside B (2 ), 5 β, 8 β -syrretaglucone C(3 ), 5 β, 8 α -syrretaglucone C (4 ), together with eight known secoiridoids (5 –12 ), were isolated from the stem barks of Syringa reticulata (Bl.) Hara. The structures of isolated compounds were established based on the physical and chemical means, NMR spectroscopy, high-resolution mass spectrometry (HR-ESI-MS), and circular dichroism spectrum (CD), as well as in comparison with the literature. The cytotoxicity of isolated compounds was investigated using CCK8 assay, which showed that these compounds had different degrees of inhibitory effect on two human tumor (MGC803, LN229) cell lines. GRAPHICAL ABSTRACT: UF0001